Comparison of two confocal micro‐XRF spectrometers with different design aspects. (6th November 2013) - Smolek, S.; Nakazawa, T.; Tabe, A.; Nakano, K.; Tsuji, K.; Streli, C.; Wobrauschek, P.
<x xml:space="preserve">Abstract</x> Two different confocal micro X‐ray fluorescence spectrometers have been developed and installed at Osaka City University and the Vienna University of Technology Atominstitut. The Osaka City University system is a high resolution spectrometer operating in air. The Vienna University of Technology Atominstitut spectrometer has a lower spatial resolution but is optimized for light element detection and operates under vacuum condition. The performance of both spectrometers was compared. In order to characterize the spatial resolution, a set of nine specially prepared single element thin film reference samples (500 nm in thickness, Al, Ti, Cr, Fe Ni, Cu, Zr, Mo, and Au) was used. Lower limits of detection were determined using the National Institute of Standards and Technology standard reference material glass standard 1412. A paint layer sample (cultural heritage application) and paint on automotive steel samples were analyzed with both instruments. The depth profile information was acquired by scanning the sample perpendicular to the surface. © 2013 The Authors. X‐Ray Spectrometry published by John Wiley & Sons, Ltd.